2006
DOI: 10.1001/archopht.124.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Age-Related Maculopathy in Older Europeans

Abstract: To estimate the prevalence of age-related maculopathy in an older population from 7 European countries.Methods: Randomly sampled people 65 years and older were invited to an eye examination in centers across 7 European countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
245
7
15

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(283 citation statements)
references
References 32 publications
16
245
7
15
Order By: Relevance
“…The mean age at presentation was 78.45±7.29 years (range 62 to 91 years). The mean number of intravitreal injections before PIAE was 5.2 ± 3.6 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The mean number of days from injection to presentation was five (range 1-39).…”
Section: Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age at presentation was 78.45±7.29 years (range 62 to 91 years). The mean number of intravitreal injections before PIAE was 5.2 ± 3.6 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The mean number of days from injection to presentation was five (range 1-39).…”
Section: Patient Demographicsmentioning
confidence: 99%
“…[1][2][3][4] This can have a significant impact on quality of life for the individual and cause a significant economic burden. 5 The exudative form accounts for 10% of ARMD cases with an estimated incidence of 0.45 per 1000.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] An estimated 13 million Americans have some degree of AMD and unless better preventive treatments emerge, this number is expected to climb and even reach epidemic proportions with the overall aging demographics. Although the cause of AMD has not yet been fully determined, this complex multifactorial disease clearly results from the interplay of multiple genetic and environmental risk factors 2,5 that lead to progressive destruction of retinal pigment epithelial (RPE) cells and photoreceptors and ultimately to vision loss.…”
mentioning
confidence: 99%
“…The prevalence of AMD in this study was lower than that reported in the Beaver Dam (BDES, 1.2%, males), Rotterdam (RS, 1.4%, males), Blue Mountains Eye Study (BMES) (1%, males), Chesapeake Bay Watermen (1.3%), the European eye study (EUREYE, 2.5%, males), the Eye diseases prevalence research group (Eye diseases PRG, 0.63-3.97%, white males), Cardiovascular health study (CHS, 1.4%, white males), and Melton Mowbray (1.9% exudative AMD, 1.9% GA), 1,4,[33][34][35][36][37][38] but it is comparable to the Visual Impairment Project 39 (VIP, 0.58%, males) and the Colorado-Wisconsin Study 40 (0.53%, age-standardised to VIP study). In part this may be due to differences in grading between studies; however, the grading system used in our study was almost identical to that used in the RS.…”
Section: Discussionmentioning
confidence: 99%
“…3 As life expectancy in the developed world increases, the prevalence and incidence of blindness from this disease will undoubtedly rise unless preventive strategies or treatments are found. Several studies have examined the prevalence of ARM/ AMD in the United Kingdom, [4][5][6][7][8][9][10][11][12] but only two community-based studies have had a sample size of more than a thousand participants, 13 and one was restricted to general practice patients over 75 years. 14 Identifying those at high-risk of developing AMD is crucial in preventing irreversible visual impairment and blindness from this disease, and may lead to secondary/tertiary prevention strategies.…”
Section: Introductionmentioning
confidence: 99%